ANALYSIS OF ERRORS OF ELEVENTH SCIENCE 1 NATIONAL SENIOR HIGH SCHOOL 1 MIDDLE MALUKU IN RESOLVING TRIGONOMETRY FUNCTION LIMIT PROBLEMS AND REMEDIATION EFFORTS - Shafriaty Kepa; Hartati Ramli (Universitas Brawijaya, 2021)
This study was a qualitative descriptive research which aimed to describe the types of errors made by students of class of eleventh science 1 National Senior School 1 Maluku Tengah in solving the trigonometric function limit questions. Also, to determine the factors that cause students to make these mistakes and discover how remedial affects the error. The subjects of this study were students of eleventh science 1 National Senior School 1 Maluku Tengah. Student error data is obtained from the results of the diagnostic test answers identified into the types of errors. After that, four students were selected to be interviewed. Based on the results of data analysis and research results it can be concluded as follows: (1) The students' mistakes in solving the trigonometric function limit problems were errors using definitions or theorems and solutions that were not rechecked. (2) The factors that cause students done the limit of trigonometric functions task incorrectly are students have not mastered the prerequisite material, which plays an essential role in the process of understanding the concept of limit trigonometric functions. Such as the basic concepts of limit functions and trigonometry, students do not memorize basic trigonometric formulas. So that they find it challenging to work on questions; students do not understand the basic concepts of limit trigonometric functions. Students are confused when determining which part of the problem to change first or students are confused when describing questions. Students do not know what steps to use in solving math problems; the time used teachers in teaching in the classroom are too little so that students do not practice questions during the learning process in class. (3) After comparing the results of the diagnostic test and the student's remedial test, it can be seen that there is an increase in student learning outcomes on the subject of limit trigonometric functions.